‘We are all in the same boat’: a qualitative cross-sectional analysis of COVID-19 pandemic imagery in scientific literature and its use for people working in the German healthcare sector - Baranowski, Andreas M.; Blank, Rebecca; Maus, Katja; Tüttenberg, Simone C.; Matthias, Julia-K.; Culmann, Anna C.; Radbruch, Lukas; Richter, Cornelia; Geiser, Franziska (Frontiers in Psychiatry, 2024)
The COVID-19 pandemic presents a significant challenge to professional responders in healthcare settings. This is reflected in the language used to describe the pandemic in the professional literature of the respective professions. The aim of this multidisciplinary study was to analyze the linguistic imagery in the relevant professional literature and to determine the identification of different professional groups with it and its emotional effects.Method: A list of 14 typical, widespread and differing imageries for COVID-19 in form of single sentences (e.g., "Until the pandemic is over, we can only run on sight.") were presented to 1,795 healthcare professionals in an online survey. The imageries had been extracted from a qualitative search in more than 3,500 international professional journals in medicine, psychology and theology.Ratings of agreement with these imageries and feelings about them were subjected to factor analysis.Based on the list of imageries presented, it was possible to identify three factors for high/low agreement by experiences, and two factors for high/low induced feelings. Broad agreement emerged for imageries on "fight against the crisis" and "lessons learned from the crisis", while imageries on "acceptance of uncontrollability" tended to be rejected. Imageries of "challenges" tended to lead to a sense of empowerment among subjects, while imageries of "humility" tended to lead to a sense of helplessness.Conclusions: Based on the qualitative and subsequential quantitative analysis, several factors for imageries for the COVID-19 pandemic were identified that have been used in the literature.Agreement with imageries is mixed, as is the assessment of how helpful they are.